Physical activity moderated the mediating effect of self-control between bullying victimization and mobile phone addiction among college students - Yang Liu; Dan Tan; Pengfei Wang; Ting Xiao; Xubo Wang; Tiancheng Zhang (Scientific Reports, 2024)
Abstract This study aims to investigate the relationship between bullying victimization and mobile phone addiction (MPA) among college students, taking into consideration the mediating role of self-control and the moderating role of physical activity. A self-report survey was administered to college students from 4 universities in Guangxi, Liaoning, and Hunan provinces in China. Participants were asked to report their experiences of bullying victimization, level of MPA, self-control, and physical activity. Descriptive statistics, correlation analysis, and regression analysis were conducted to analyze the data. Mediation and moderation models were subsequently established to examine the relationships between variables. The results indicated a positive correlation between bullying victimization and MPA among college students. Additionally, bullying victimization was negatively correlated with self-control. Bullying victimization significantly predicted MPA, and self-control partially mediated this relationship. Furthermore, physical activity moderated the association between bullying victimization and self-control among college students. The findings suggest that self-control plays a partial mediating role in the relationship between bullying victimization and MPA among college students. Moreover, physical activity weakens the association between bullying victimization and self-control. Therefore, promoting physical activity to reduce MPA among college students who have experienced bullying victimization is highly recommended.